Three waves of extended mind theories and urban planning: the city as a distributed socio-cognitive architecture - Candeloro, Giulia; Mastrolonardo, Luciana; Angrilli, Massimo; Crociata, Alessandro; Sacco, Pier Luigi (Frontiers in Built Environment, 2024)
This article explores the intersection between cognition theories and urban planning, conceptualizing the city as a distributed socio-cognitive architecture. It traces the evolution of these theories through three waves—functionalism, social externalism, and radical enactivism —. Correspondingly, the article suggests implications for reorienting urban planning approaches, highlighting participatory design, collaborative placemaking, and the nurturing of place-based affordances. Drawing examples from existing planning literature, it demonstrates resonances with Extended Mind-informed orientations. The conclusion synthesizes these insights, proposing a potentially transformative framework by rethinking planning as more participatory, pluralistic, and cognitively integrative, challenging internalist and technocratic assumptions.